Paranoid psychosis after a single parenteral dose of indomethacin administered for headache diagnosis: A case and review of the literature - Nazia Karsan; Ray Pyari Bose; Peter J Goadsby (SAGE Publishing, 2024)
Background: Indomethacin is a non-steroidal anti-inflammatory used to diagnose and treat hemicrania continua and paroxysmal hemicrania. Treatment can be complicated by gastrointestinal adverse effects; less commonly reported are idiosyncratic neuropsychiatric adverse effects with indomethacin. Methods: A 50-year-old male with lateralized brief attacks of headache associated with cranial autonomic symptoms was administered a single 200 mg dose of intramuscular indomethacin. Within an hour, he developed acute psychosis, with paranoid delusions and verbal and physical aggression lasting 5 h, followed by recovery to baseline. We used search terms "indomethacin psychosis," "indomethacin psychiatric," "indomethacin side effects," "non-steroidal anti-inflammatory psychosis," and "non-steroidal anti-inflammatory psychiatric" within PubMed to identify previous reports and literature in this area. Results: Neuropsychiatric adverse effects of indomethacin have been reported since 1965 in a dose-dependent manner, usually with oral courses. They may be more common in the elderly, postpartum women and postoperative patients. Conclusion: Neuropsychiatric adverse effects should be considered in headache medicine, particularly in at-risk groups when indomethacin is administered. Patients, particularly those at highest risk, should be counseled about the risk of neuropsychiatric side effects on indomethacin which may be dose-dependent and are generally reversible on stopping the drug.